1975
DOI: 10.1113/jphysiol.1975.sp011071
|View full text |Cite
|
Sign up to set email alerts
|

Discharges of relay cells in lateral geniculate nucleus of the cat during spontaneous eye movements in light and darkness.

Abstract: 3. Following saccades occurring in the light, T and M cells showed a burst discharge, while spontaneous discharges of S cells were completely suppressed for 150-200 msec. 4. When tested in total darkness, modifications in activity which were apparent in light disappeared completely. This was true for all 315 relay cells.5. T cells responded to optic chiasm stimulation at shorter latencies (X = 1.15 msec) than S cells (X = 1P77 msec). M cells showed a latency distribution in between those for S and T cells wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1976
1976
2002
2002

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…The latter is strong evidence for central changes of visual processing during saccadic eye movements, and we show that such changes are manifest in MT and MST. Previous studies addressing the effects of saccadic eye movements on visual processing provided somewhat equivocal results and generally failed to show direct evidence of saccadic suppression (23)(24)(25)(26)(27). Our data from MT and MST demonstrate that saccadic suppression is evident in a substantial fraction of directionselective cells-they exhibit reduced activity when image motion is due to a saccade.…”
mentioning
confidence: 57%
“…The latter is strong evidence for central changes of visual processing during saccadic eye movements, and we show that such changes are manifest in MT and MST. Previous studies addressing the effects of saccadic eye movements on visual processing provided somewhat equivocal results and generally failed to show direct evidence of saccadic suppression (23)(24)(25)(26)(27). Our data from MT and MST demonstrate that saccadic suppression is evident in a substantial fraction of directionselective cells-they exhibit reduced activity when image motion is due to a saccade.…”
mentioning
confidence: 57%
“…This question was rendered controversial by the failure of NODA [23] to reproduce these results. In alert cats, this author was unable to show any significant modification of geniculate cells activity during spontaneous eye movements in the dark, although important changes appeared when the eye movements occurred in front of an illuminated grating.…”
Section: Genieulo-cortical Pathwaymentioning
confidence: 99%
“…Hence, TSVMOTO and SuzuKI suggest that the influence of saccades on LGd may be twofold. First, during the early part of the saccade X cells receive a strong inhibition from the Y system, produced by the rapid shift of the visual image on the retina [23,37]. Second, during the late part of the saccade, X cells are facilitated by an extra-retinal influence which cancels X cells inhibition and thus improves transmission of foveal vision through LGd.…”
Section: Genieulo-cortical Pathwaymentioning
confidence: 99%
“…Barlow et al (1977) have suggested that the shift effect might signal the occurrence of saccadic eye movements and therefore be instrumental in 'saccadic suppression' (McKay, 1970;Brooks & Fuchs, 1975). Furthermore, since Y cells in the cat lateral geniculate nucleus inhibit X cells (Singer & Bedworth, 1973) and since some cells in the lateral geniculate of the conscious cat are inhibited by eye movements over a patterned visual field (Noda, 1976), they suggested that saccadic suppression might involve Y cell inhibition of X cells. Although Y cells in the lateral geniculate nucleus did have a prominent shift effect, we found little evidence for interaction between peripheral stimuli and stimuli delivered to the receptive field in either X or Y cells.…”
Section: Properties Of X and Y Neuroses In The Lateral Geniculate Nucmentioning
confidence: 99%